Effect of carbon nanofibre orientation on fatigue properties of carbon fibre-reinforced polymers. (March 2023) - Mrzljak, Selim; Zanghellini, Benjamin; Gerdes, Lars; Helwing, Ramon; Schuller, Reinhard; Sinn, Gerhard; Lichtenegger, Helga; Walther, Frank; Rennhofer, Harald
Nano-reinforcements in carbon fibre-reinforced polymer (CFRP) have proven to enhance the mechanical properties considering quasi-static, as well as fatigue load and, are a promising option with regard to CFRP performance optimisation. While general knowledge about the nanofiller content and its influence in CFRP is well documented, the use of alignment techniques for a specific orientation of the nano-reinforcements is still insufficiently studied. In this work, the influence of oriented carbon nanofibres (CNF) on the mechanical properties of bidirectional CFRP is investigated. CFRP was produced CNF-reinforced with and without orientation using a hot press, where an electric field was applied during curing. The laminates were characterised with respect to dispersion quality, pore volume, quasi-static properties (tensile and bending tests) and dynamic properties (fatigue tests). Electrical resistance measurement was applied together with digital image correlation and in situ computed tomography to generate knowledge about the fatigue-related damage evolution and evaluate the sensors for viable use of condition monitoring. Results show that the orientation of CNF has a significant impact on both quasi-static and fatigue properties, increasing the strength while reducing and slowing down the introduced damage. Orientation of nanofillers thus shows large optimization potential of mechanical properties of CFRP components.